2019
DOI: 10.1016/j.chemosphere.2018.12.090
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of gold nanoparticles in the gilthead seabream (Sparus aurata) after single exposure and combined with the pharmaceutical gemfibrozil

Abstract: Widespread use of pharmaceuticals and suboptimal wastewater treatment have led to increased levels of these substances in aquatic ecosystems. Lipid-lowering drugs such as gemfibrozil, which are among the most abundant human pharmaceuticals in the environment, may have deleterious effects on aquatic organisms. We examined the genotoxicity of gemfibrozil in a fish species, the gilthead seabream (Sparus aurata), which is commercially important in southern Europe. Following 96-h waterborne exposure, molecular (ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…DNA strand breaks and chromosomal fragmentation, and oxidative stress in Arbacia lixula embryos exposed to CuO NPs were reported [4,10]. We found that C-NPs were genotoxic to P. lividus embryos as detected by comet assay, which is generally the preferred method due to its capacity to detect low levels of DNA damage as reported by comparing eight different genotoxicity assays [30,45].…”
Section: Discussionmentioning
confidence: 82%
“…DNA strand breaks and chromosomal fragmentation, and oxidative stress in Arbacia lixula embryos exposed to CuO NPs were reported [4,10]. We found that C-NPs were genotoxic to P. lividus embryos as detected by comet assay, which is generally the preferred method due to its capacity to detect low levels of DNA damage as reported by comparing eight different genotoxicity assays [30,45].…”
Section: Discussionmentioning
confidence: 82%
“…The data showed that the acute and chronic administration of Au-NPs led to higher levels of DNA damage in the cerebral cortex compared with the negative control [15]. Fish were exposed to Au-NPs (4, 80 and 1600 μg/l) for 96 h and DNA damage in blood cells from the posterior cardinal vein, as evaluated by a comet assay, was significantly increased in the Au-NP-treated group compared with the control group [16]. In the study by Schulz et al, rats were administered Au-NPs by a single intratracheal instillation in the lung for 72 h, after which alveolar lung cells were isolated and subjected to a comet assay.…”
Section: In Vivo Comet Assaymentioning
confidence: 96%
“…Genotoxic effects of Au NPs have been observed even at concentrations as low as 4 μg•l -1 in gilthead seabream (Sparus aurata) exposed to citrate and PVP coated Au NPs for 96 h. Nanoparticles have induced DNA damage (erythrocyte DNA strand breaks), the frequency of erythrocytic nuclear abnormalities was also increased (Barreto et al 2019). Alteration of gene expression levels, mutations, and mitochondrial dysfunction was observed in zebrafish exposed to citrate capped Au NPs (sized 12 nm and 50 nm) in their diet, over the period of 36 and 60 days.…”
Section: Goldmentioning
confidence: 99%